ANALISIS PSIKOLOGI SASTRA TERHADAP PEMAKNAAN TOKOH MAHASISWA DALAM PUISI TAKUT 66, TAKUT 98 KARYA TAUFIQ ISMAIL - Ragil Prayogi, Kukuh; Afrilia, Regi Murni; Pasaribu, Marco Julio Hotnaldy (Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study investigates the characterization of students in Taufiq Ismail’s poems Takut 66 and Takut 98 through the framework of Sigmund Freud’s psychoanalytic theory, focusing on the id, ego, and superego. A descriptive qualitative method was used, with data consisting of words, phrases, clauses, and sentences that reveal personality traits and characterization techniques within the poems. The analysis demonstrates a balanced representation of the three personality structures. The id is reflected in students’ expressions of disappointment and anger toward governmental leadership. The ego emerges in the form of fear directed at lecturers, who function as enforcers of rules and constraints within the academic setting. The superego is manifested in students’ moral conscience, which drives them to protest as an expression of unrest, discomfort, and dissatisfaction with the highest governmental authority, the president.